Pollinosis in children and adolescents: modern aspects of pathogenesis and tendencies in therapy - I. I. Balabolkin (Аллергология и Иммунология в Педиатрии, 2023)
The development of pollinosis in children and adolescents is determined by the influence of genetic and environmental factors. The pathogenetic basis of pollinosis in children and adolescents is the differentiation of Th0 to Th2, activation of Th2cells and increasing of the production of IL-4, IL-5, IL-13, sIgE, activation of mast cells, basophils, eosinophils, with following development of IgE-mediated allergic reaction after exposure to pollen allergens and the manifestation of clinical symptoms of pollinosis (allergic rhinitis, allergic conjunctivitis, bronchial asthma). Children and adolescents with pollinosis often develop cross-allergic reactions to plant-based foods. Pathogenetic pharmacotherapy (antihistamines of the second generation, topical corticosteroids, antileukotrienes, decongestants) allows to achieve control over the symptoms of pollinosis. Subcutaneous and sublingual ASIT are high effective, they reduce the severity of symptoms of pollinosis, decrease the risk of developing bronchial asthma and severe clinical forms of pollinosis. The sublingual ASIT is more safe than subcutaneous ASIT.